Pembuatan Microcarrier Berbahan Baku Hidroksiapatit Menggunakan Metode Protein Foaming-Starch Consolidation - pertiwi, Megawati Dwi; Fadli, Ahmad; Drastinawati, Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Macroporoous microcarrier is one of tissue engineering technology that consist of support matrix and can be used as a cell culture medium in bioreactor. Protein foaming-starch consolidation method is choosed for manufacturing porous hydroxyapatite with egg yolk as a pore-forming agent. The purpose of this study was to determined the effect of yolk addition, sintering temperature, and drying temperature on the physical, chemical and mechanical properties of porous hydroxyapatite made by protein foaming-starch consolidation method. This research was begun with mixing the hydroxyapatite powder, starch, Darvan 821A and yolk. S;urry was stirred mechanically in speed of 150 rpm for 3 hours. Slurry was poured in mold and heated in oven with the temperature of 180ºC for an hour. Then sample was released from mold and burnt at 600ºC ended by sintering at 1250ºC for an hour. The experimental resulted porous hydroxyapatite with average pore size differs from 13.7-17.9 μm, degree of porosity 59.3-63.6 % and compressive strength 5.17-8.2 MPa.Keywords: hydroxyapatite, microcarrier, protein foaming-starch consolidation